2011
DOI: 10.4314/wsa.v37i1.64102
|View full text |Cite
|
Sign up to set email alerts
|

Application of the mixture design to decolourise effluent textile wastewater using continuous stirred bed reactor

Abstract: Important pollutants in textile effluents are mainly recalcitrant organics, colours, toxicants and inhibitory compounds, surfactants, chlorinated compounds (AOX), pH and salts. An aerobic system using a continuous stirred bed reactor (SBR) was continuously operated at constant temperature and fed with textile wastewater (pH 7 and total chemical oxygen demand (COD) 1 700 mg/ℓ).This report is focused on the decolourisation treatment of effluent by a bacterial consortium (Sphingomonas paucimobilis, Bacillus sp. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
(3 reference statements)
1
22
0
2
Order By: Relevance
“…Although the results were unexpected for color and aromatic amines removal, microaeration would be very important to remove other compounds present in textile wastewater, such as adsorbable organic halides (AOX), which are recalcitrant under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results were unexpected for color and aromatic amines removal, microaeration would be very important to remove other compounds present in textile wastewater, such as adsorbable organic halides (AOX), which are recalcitrant under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works showed that the Malachite Green and Crystal Violet degradation into leucomalachite and leucocrystal violet are equally toxic to the initial compound (Ayed et al . 2010b,d).…”
Section: Resultsmentioning
confidence: 99%
“…The textile industry is the largest user of synthetic dyes consuming about 56% of the total annual world production (7 × 10 5 tons) (Ayed et al . 2010d, 2011a,b). Azo dyes are characterized by one or more azo bonds (N = N) as chromophore, usually linked to benzenic or naphthalenic rings containing lateral OH and/or SO 3 groups (Garcia‐Segura & Brillas ).…”
Section: Introductionmentioning
confidence: 99%
“…MBR s stem n n tasarımında, l teratürde tekst l atıksuyu arıtımı üzer ne yapılan deneysel çalışmalarda bel rt len tekst l atıksuyunun k rl l k yükler [13,14] V6.2.1'de yapılmıştır. Programlamada, 4 tane ekran tasarlanmıştır.…”
Section: Membran Bi̇yoreaktör Tasarim Hesaplamalari (Membrane Bi̇oreactunclassified